Identification of Avian Leukosis Virus from layer chicken by serological test and embryo inoculation technique (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
The present study was designed with a view to identify the Avian Leukosis Virus (ALV) by direct Enzyme Linked Immunosorbent Assay (ELISA) as well as to know the prevalence of ALV in different age groups of layer birds at Dinajpur district of Bangladesh. The birds were categorized into three groups, namely group A (brooder) included bird aged 13 days, group B (grower) included bird aged 16 weeks and lastly group C (layer) included bird aged 32 weeks. In this study a total of 92 cloacal swab samples were examined and 13 positive cases of ALV was found among which 5, 4 and 4 positive samples were in grower, brooding and layer chickens respectively. This study showed that ALV positive cases were 14.13% in layer birds whereas 14.5% positive cases in Sonali chicken and 13.3% in case of Hy-Line brown chicken. The inoculation of cloacal swab was done into five 10 days old embryonated chicken eggs through yolk sac route. After 5 days of inoculation death of the all embryos with haemorrhage was observed indicating the prevalence of Avian Leukosis Virus in the study area of Bangladesh. Since Avian Leukosis Virus transmitted both horizontally and vertically therefore measures to prevent spread are more demanding.Asian Australas. J. Biosci. Biotechnol. 2016, 1 (1), 23-30